2006
DOI: 10.1016/j.cub.2006.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Glial Lazarillo, a Homolog of Apolipoprotein D, Reduces Lifespan and Stress Resistance in Drosophila

Abstract: The vertebrate Apolipoprotein D (ApoD) is a lipocalin secreted from subsets of neurons and glia during neural development and aging . A strong correlation exists between ApoD overexpression and numerous nervous system pathologies as well as obesity, diabetes, and many forms of cancer . However, the exact relationship between the function of ApoD and the pathophysiology of these diseases is still unknown. We have generated loss-of-function Drosophila mutants for the Glial Lazarillo (GLaz) gene , a homolog of Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
158
2
13

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 125 publications
(180 citation statements)
references
References 30 publications
7
158
2
13
Order By: Relevance
“…ApoD is upregulated by, and protects against, oxidative stress [9,13,15]. As reported here and in other works, ApoD expression is maintained at general low levels in tumor tissues, which, along with its positive regulation by growth arrest [38], supports the proposal made by several authors that ApoD is a tumor suppressor gene [30].…”
Section: Apod Polymorphisms and Crc Risksupporting
confidence: 92%
See 2 more Smart Citations
“…ApoD is upregulated by, and protects against, oxidative stress [9,13,15]. As reported here and in other works, ApoD expression is maintained at general low levels in tumor tissues, which, along with its positive regulation by growth arrest [38], supports the proposal made by several authors that ApoD is a tumor suppressor gene [30].…”
Section: Apod Polymorphisms and Crc Risksupporting
confidence: 92%
“…Inducing OS by treatment with the ROS generator paraquat (PQ), we have demonstrated a protective function of ApoD in the organism survival. This effect was associated with a role in regulating tissue homeostasis and in maintaining low levels of lipid peroxidation [13][14][15]. We have recently shown that ApoD contributes to reduce inflammation levels in ROS-injured tissues and promotes the clearance of lipid peroxides in cells [16,17].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Null mutants of ApoD or its homologous genes show an increased amount of peroxidated lipids in whole body fly extracts (Hull-Thompson et al, 2009;Sanchez et al, 2006) or in mouse brain homogenates (Ganfornina et al, 2008). Since lipid peroxidation in cellular membranes is a major sink for reactive oxygen species (ROS), a greater amount of peroxidated lipids can be due to a higher rate of production or to a slower rate of removal/recycling of the damaged membranes.…”
Section: Apod Deficiency Increases Lipid Peroxides In Astrocytes Withmentioning
confidence: 99%
“…The homologues of ApoD in Drosophila, GLaz and NLaz, protect against oxidative damage and contribute significantly to the regulation of longevity (HullThompson et al, 2009;Ruiz et al, 2011;Sanchez et al, 2006;Walker et al, 2006). ApoD is in fact the most robust age dependent up-regulated gene in the brain, conserved across species (de Magalhaes et al, 2009;Loerch et al, 2008), and its expression is boosted by a collection of traumatic, pathological and degenerative nervous system conditions in humans (reviewed by Van Dijk et al, 2006), including Parkinson's disease (Ordonez et al, 2006;Song et al, 2009).…”
Section: Introductionmentioning
confidence: 99%